2017
DOI: 10.1080/17476348.2017.1312346
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis, part I: epidemiology, pathogenesis, and diagnosis

Abstract: Many forms of interstitial lung disease (ILD) can progress to extensive fibrosis and respiratory failure. Idiopathic pulmonary fibrosis (IPF), which generally has a poor prognosis, has been thoroughly studied over the past two decades, and many important discoveries have been made that pertain to genetic predisposition, epidemiology, disease pathogenesis, diagnosis, and management. Additionally, non-IPF forms of ILD can have radiologic and histopathologic manifestations that mimic IPF, and making an accurate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 165 publications
1
122
0
12
Order By: Relevance
“…Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease with high lethality, a fatal prognosis, and a lack of effective medical therapies [ 1 , 2 ]. The pathological characteristics of IPF mainly include the disruption of the pulmonary parenchymal matrix and replacement with fibrotic tissues [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease with high lethality, a fatal prognosis, and a lack of effective medical therapies [ 1 , 2 ]. The pathological characteristics of IPF mainly include the disruption of the pulmonary parenchymal matrix and replacement with fibrotic tissues [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies that identified evidence of inherited risk for developing pulmonary fibrosis focused on familial cases, including variants such as genes coding for mucin 5B surfactant proteins [136] or those involved in telomere homeostasis and function [73]. Studies that have focused particularly on genome-wide linkage analyses have identified numerous gene polymorphisms that are associated with increased risk for pulmonary fibrosis [135,[138][139][140]. However, not all races have been evaluated, even for widely studied genetic mutations that have demonstrated their association with pulmonary fibrosis.…”
Section: Genetics Of Pulmonary Fibrosismentioning
confidence: 99%
“…In humans, 28 types of collagens have been identi ed, and more than 1300 mutations in collagen-associated genes are linked with genetic diseases 4,6 . As with the ECM de ciency problem, excessive secretion and accumulation of ECM causes serious brotic diseases such as liver, kidney, heart and lung brosis 7,8,9 . Fibrosis that forms in solid cancer tissue is necessary or accelerated for cancer growth and metastasis 5 .…”
Section: Introductionmentioning
confidence: 99%